Analisis Sektor Basis dan Sektor Potensial Terhadap Pertumbuhan Ekonomi Kota Jambi Tahun 2014-2018 - Jesica Permata; Menik Kurnia Siwi (Universitas Negeri Padang, 2023)
The purpose of this reseach is to analyze the basic sector and potential sector in Jambi city and to make development strategy of the top sector in Jambi city. The reseach use the secondary data using 17 sectors in Jambi city, during the years 2014-2018. Data analysis technique are using Location Quotient (LQ), Shift Share (SS) and Growth Ratio Model (MRP). Base on LQ, Shift Share and MRP calculations to classify commodities, the basic and the potensial sector in Jambi city is electricity and gas supply, wholesale and retail trade, repair of cars and motorcycles, transportatio and werehousing, and company services.